Ionic liquid [Dabco-H][AcO] as a highly efficient and recyclable catalyst for the synthesis of various bisenol derivatives via domino Knoevenagel–Michael reaction in aqueous media. Issue 102 (20th October 2016) - Yang, Cheng; Su, Wan-Qi; Xu, Da-Zhen
Abstract : An efficient, green and reusable catalystic system for the synthesis of various bisenol derivatives is presented. Abstract : A simple and highly efficient domino Knoevenagel–Michael reaction procedure for the synthesis of a series of bisenols has been successfully developed. In the presence of 1, 4-diazabicyclo[2.2.2]octane (Dabco)-based ionic liquid catalysts, which are environmental friendly, inexpensive, and recyclable, the reaction afforded the corresponding bisenols compounds in excellent yields within short times in aqueous media. This green synthetic protocol is applicable to a wide range of aldehydes with enol compounds, including 4-hydroxycoumarin, 2, 4-dihydro-3 H -pyrazol-3-one, cyclohexane-1, 3-dione, Meldrum's acid, 2-hydroxy-1, 4-naphthoquinone (Lawsone) and their derivatives. This method is readily amenable to large-scale synthesis. The use of water as the reaction medium makes the process environmentally benign. Moreover, water is the only byproduct. The catalysts can be recycled five times without activity loss.